(untitled) - Warner, Seth (New Jersey, 1965)
This text is intended primarily for juniors and seniors seeking an introduction to modern, abstract algebra. It may also prove useful for beginning graduate students unprepared in modern algebra.
Keywords: Algebra,Đại số